Efficacy of a Media Literacy Intervention for Indoor Tanning Prevention. Issue 7 (3rd July 2018) - Cho, Hyunyi; Yu, Bing; Cannon, Julie; Zhu, Yu Michael
Abstract : Indoor tanning leads to melanoma, the fifth most common cancer in the USA. The highest rate of indoor tanning is among young women whose exposure to tanned images in the media is linked to protanning attitudes. This study evaluated the efficacy of a media literacy intervention for reducing young women's indoor tanning. Intervention participants analyzed the content and functions of the media influencing protanning attitudes and produced counter-messages to help themselves and peers resist harmful media effects. The message production was of two types: digital argument production or digital story production. The control group received assessments only. This three-group randomized design involved 26 sorority chapters and 247 members in five Midwestern states where indoor tanning is prevalent. At 2- and 6-month follow-up assessments, those in the two intervention conditions were less likely to be indoor tanners ( p = .033) and reported lower indoor tanning intentions ( p = .002) compared to those in the control condition. No difference between the two intervention groups was found for behavior. Although the argument group exhibited slightly weaker indoor tanning intentions than the story group, the difference was not significant. The results provide the first evidence of the efficacy of a media literacy intervention for indoor tanning reduction. Implications for participative engagement interventions are discussed.